The influence of project-based learning assisted by augmented reality-based photosynthesis diorama on improving learning outcomes - Herowati, Desi Indah; Titi Andaryani, Eka (Jurnal Prima Edukasia, 2026)
This study investigated the effect of AR-based diorama-assisted project-based learning on fourth-grade students’ understanding of photosynthesis and learning outcomes at Kalibanteng Kidul 01 Elementary School. A quasi-experimental non-equivalent control group design was employed, involving 60 Grade 4 students divided into an experimental group and a control group. The experimental group received instruction through project-based learning supported by an AR-based photosynthesis diorama, while the control group was taught using conventional instructional methods. Data were collected through pretests and posttests and analysed using normality and homogeneity tests, independent-samples t-tests, and N-Gain analysis. The results showed that the data met the assumptions of normality and homogeneity. The independent samples t-test indicated a statistically significant difference in posttest learning outcomes between the experimental and control groups (t = −5.088, p < 0.05). In addition, the experimental group achieved a higher mean posttest score and a higher N-Gain value than the control group. These findings demonstrated that AR-based diorama-assisted project- based learning was more effective than conventional instruction in improving students’ understanding of photosynthesis and learning outcomes.